ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM PENINGKATAN EFISIENSI PADA PELAYANAN RAWAT INAP PADA RUMKIT TK II PUTRI HIJAU MEDAN - Ega Elteresia Br Ginting; Lamria Sagala; Ivo M. Silitonga (JURNAL MANAJEMEN, 2022)
The purpose of this study was to determine the application of accounting information systems in increasing efficiency in inpatient services used by the company, and to determine the impact received by management after implementing accounting information systems in inpatient services, as well as to determine the clear form of service efficiency. This research was conducted at Rumkit TK II Putri Hijau Medan. The research method used in this research is descriptive method, namely by collecting the data obtained then describing and analyzing it so that it can produce information that can be used in solving problems. The type of data used is primary data, namely data that has not been processed by the hospital and secondary data obtained from hospital report data. Based on the results of the research conducted, the authors can be concluded that the application of accounting information systems at Rumkit TK II Putri Hijau Medan is still inefficient, namely the absence of a routine maintenance schedule for accounting information systems and there are still deficiencies in the system for inputting data as a whole.